Continuing education practices in primary health care for addressing users with tuberculosis - Letícia Vieira Lourenço; Karla Santa Cruz Coelho; Emerson Elias Merhy (Salud Colectiva, 2023)
Interruption of tuberculosis treatment constitutes one of the obstacles to disease control. The standards established in health policies, at times, prove to be inflexible, tending to obscure the difficulties experienced by individuals in treatment. The aim of this article is to analyze the practices of continuous health education developed by family health teams at healthcare units in Maré, Rio de Janeiro, Brazil, in cases of tuberculosis treatment interruption. An exploratory qualitative study was conducted with twelve healthcare professionals from the team between August and November 2021. The findings from this research regard continuous health education as a strategy to enhance care processes, fostered through the lived experiences of the healthcare workers, enabling the creation of knowledge and exchanges that expand the effective treatment of tuberculosis with creativity and flexibility in the dynamics of interactions with users. This care takes place in the live work in action, whether in the hallways of healthcare units or within the community, as it occurs in real-time practice.